2016
DOI: 10.1074/jbc.m115.709493
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamin-related Protein 1 Inhibition Mitigates Bisphenol A-mediated Alterations in Mitochondrial Dynamics and Neural Stem Cell Proliferation and Differentiation

Abstract: The regulatory dynamics of mitochondria comprises well orchestrated distribution and mitochondrial turnover to maintain the mitochondrial circuitry and homeostasis inside the cells. Several pieces of evidence suggested impaired mitochondrial dynamics and its association with the pathogenesis of neurodegenerative disorders. We found that chronic exposure of synthetic xenoestrogen bisphenol A (BPA), a component of consumer plastic products, impaired autophagy-mediated mitochondrial turnover, leading to increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 70 publications
(103 reference statements)
5
50
0
Order By: Relevance
“…Autophagy may play an important role in the development of NSCs under physiological condition . NSCs differentiation fate was dependent on specific pathology as well as autophagic conditions and even on different concentration of Mel . Here, we found that HG triggered early differentiation of NSCs into neurons and astrocytes, whereas Mel effectively opposed HG‐mediated differentiation, especially neurogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…Autophagy may play an important role in the development of NSCs under physiological condition . NSCs differentiation fate was dependent on specific pathology as well as autophagic conditions and even on different concentration of Mel . Here, we found that HG triggered early differentiation of NSCs into neurons and astrocytes, whereas Mel effectively opposed HG‐mediated differentiation, especially neurogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…This suggestion was in accordance with several previous studies relating to the antioxidant benefit of NAC. A recent study showing the inhibition of ROS generation by NAC significantly reduced DRP1 levels in BPA treated NSC‐derived neuron cultures . NAC has also been shown to enhance the complex I activity of the electron transport chain in an in vitro study using synaptic mitochondria isolated from old mice through the protection of protein sulfhydryl groups of this enzyme complex from the inhibitory effect of increased reactive oxygen species .…”
Section: Resultsmentioning
confidence: 96%
“…Investigations both in vitro and in vivo have reported that BPA was able to disrupt electron transport chain, decrease ATP synthesis, increase ROS production with subsequent oxidative injury, impair mitochondrial ultrastructure, induce permeability transition, and release proteins that lead to activation of apoptosis . Regarding the role of BPA on mitochondrial homeostasis, recent evidence has shown that chronic BPA exposure impaired mitochondrial dynamics, leading to increased oxidative stress, mitochondrial fragmentation, and apoptosis in hippocampal neural stem cells . All these effects of BPA may cause the mitochondria of the BPA‐exposed group to be more easily affected by ischemia–reperfusion than those exposed to the vehicle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations